1998
DOI: 10.1161/01.atv.18.7.1119
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Fish and n-3 Fatty Acid Intake With Hemostatic Factors in the Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: Abstract-Hemostatic factors play an important role in the complications of ischemic heart and vessel disease. Dietary fats such as n-3 fatty acids have been shown to possibly influence hemostatic factors. However, most studies reporting an inverse association between cardiovascular disease and fish and n-3 fatty acid consumption used supplemental doses of fish oil or intakes exceeding the typical amount consumed by the US population. This report examined the associations of usual intakes of fish, linolenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 38 publications
2
29
0
2
Order By: Relevance
“…72 Although omega-3 fatty acid intake has been negatively associated with levels of 73 more recent evidence from the Coronary Artery Risk Development In young Adults (CARDIA) study found no significant associations between customary intakes of fish (4 to 39 g/d) and omega-3 fatty acids (0.9 to 4.1 g/d) and these coagulation factors. 74 Marckmann et al 75 also found no effect of omega-3 fatty acids (0.9 g/d) on levels of Factor VII, fibrinogen, endogenous fibrinolysis, ␤-thromboglobulin, and von Willebrand factor. In contrast, a recent study reported that coronary patients taking 5.1 g/d of omega-3 fatty acids for 6 months experienced a reduction in von Willebrand factor (128% versus 147% for controls) and thrombomodulin (25 versus 33 ng/mL).…”
Section: Thrombosis and Hemostasismentioning
confidence: 97%
“…72 Although omega-3 fatty acid intake has been negatively associated with levels of 73 more recent evidence from the Coronary Artery Risk Development In young Adults (CARDIA) study found no significant associations between customary intakes of fish (4 to 39 g/d) and omega-3 fatty acids (0.9 to 4.1 g/d) and these coagulation factors. 74 Marckmann et al 75 also found no effect of omega-3 fatty acids (0.9 g/d) on levels of Factor VII, fibrinogen, endogenous fibrinolysis, ␤-thromboglobulin, and von Willebrand factor. In contrast, a recent study reported that coronary patients taking 5.1 g/d of omega-3 fatty acids for 6 months experienced a reduction in von Willebrand factor (128% versus 147% for controls) and thrombomodulin (25 versus 33 ng/mL).…”
Section: Thrombosis and Hemostasismentioning
confidence: 97%
“…The exact mechanisms by which n-3 PUFAs exert their bene®cial effects, however, remains to be elucidated. Fish oil has been reported to favourably modulate lipoprotein metabolism (Connor et al, 1993), haemostatic factors (Archer et al, 1998), and blood pressure (Morris et al, 1993). Dietary n-3 fatty acids have also been reported to reduce mechanically induced lesion formation in animal models (Zhu et al, 1988), an observation which may be, at least partially, explained by the effect of ®sh oil on growth factor levels.…”
Section: Introductionmentioning
confidence: 99%
“…High intake of marine animals and fish rich in n-3 FA is known to have an antiatheromatous effect 15,16) . Fish consumption and serum n-3 FA levels have been associated with the reduced risk of coronary heart disease after controlling for other coronary risk factors [17][18][19] , whereas some studies failed to find the inverse association 20,21) . It is uncertain whether increased n-6 FA reduces the risk of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%